A Systematic Literature Review of Pancasila Education in Higher Education: Trends, Pedagogical Innovations, and Learner Competencies - Ali Miftakhu Rosyad; Siti Fatahiyah Mahamood (Sultan Publisher, 2025)
Pancasila education has become increasingly critical in Indonesian higher education as institutions grapple with globalization, digital transformation, and the need to preserve national identity. This systematic literature review addresses a critical gap in civic education scholarship by mapping pedagogical innovations and synthesizing empirical evidence on learner competency development in Pancasila educationan area previously examined only through single-institution case studies. Using the PRISMA framework, this study analyzed 45 peer-reviewed articles published between 2015 and 2024 from major academic databases. Results reveal that active, experiential pedagogies (project-based learning, service-learning, dialogical approaches) consistently demonstrate superior effectiveness compared to traditional lecture-based instruction, with effect sizes ranging from d=0.62 to d=1.42 for applied competencies, though these findings are based predominantly on short-term, self-reported outcomes. Five core competencies emerge from effective programs: civic knowledge, ethical reasoning, critical thinking, cultural awareness, and social responsibility. The review's primary contribution lies in providing the first systematic synthesis of pedagogical effectiveness evidence across diverse Indonesian contexts, revealing that implementation quality and contextual factors significantly moderate outcomes. However, substantial gaps remain in longitudinal behavioral assessment and cross-institutional comparative research. These findings suggest that effective Pancasila education requires contextualized, student-centered approaches that integrate cognitive, affective, and behavioral dimensions, though claims of long-term effectiveness must remain tentative given current methodological limitations.